Efficiency and size - comments and extensions - Todd, D. (Economic & Social Studies, 1977)
A recent contribution to this Review considered a number of measures of business efficiency and applied these to a sample of firms in the Irish Plastics Industry. The purpose of this note is to extend the analysis somewhat further and to draw attention to some features of the efficiency measures chosen.
Keywords: Business efficiency; Plastics industry